Service Quality Measurement through Higher Education Performance (HEDPERF) The Case of an Indonesian Public University - Yuli Purwanto; Irwan Noor; Andriani Kusumawati (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The purpose of this study was to measure service quality performance based on student perceptions of the higher education department service quality performance. The research used a Higher Education Performance (HedPERF) measurement scale. There were six structural factors/dimensions namely: Non-Academic Aspect, Academic Aspect, Reputation, Access, Program Issues, and Understanding. The research method used quantitative methods with descriptive approaches. The research utilized questionnaire surveys with Probability Sampling techniques and Proportioned Stratified Random Sampling collection techniques. Data analysis utilized Importance Performance Analysis. The importance-performance analysis result exhibited similarities in measurement results. The similarities occurred between respective service items measurements and factors/dimensions structure instrument measurement. The analysis result exhibited that Academic Aspect factors are service quality improvement’s top priority, Reputation and Access factors are maintained service quality, Understanding factors are service quality improvement’s secondary priority, and Non-Academic Aspect factors exhibited service quality exceeding students expectations. To improve Academic Aspect factor, it is suggested to implement Law No. 14 of 2005 which focused on lecturer competencies (Pedagogic Competence, Professional Competence, Social Competence, and Personality Competence).